Evaluation of preconcentration methods in the analysis of synthetic musks in whole‐water samples. Issue 13 (19th May 2015) - Cavalheiro, Joana; Prieto, Ailette; Zuloaga, Olatz; Preudhomme, Hugues; Amouroux, David; Monperrus, Mathilde
<x xml:space="preserve">Abstract</x> According to the European Water Framework Directive, environmental assessment of organic compounds should be made in whole‐water samples, but due to their hydrophobicity and strong attraction to organic content these compounds can be found bound to suspended particle matter or in the dissolved fraction. In this work, the extraction of musk compounds was studied in whole‐water samples exhibiting different amounts of dissolved organic carbon and suspended particulate matter using polyethersulfone preconcentration technique. Matrix effects in estuarine and wastewater (both influent and effluent) were evaluated for filtered and unfiltered samples. For unfiltered samples, estuarine water exhibited matrix effects <20%, while for effluent it was up to 48% and for influent ranged from 85 to 99%. To compensate matrix effects and determine total concentrations in unfiltered samples, different quantification approaches were tested: the use of deuterated analogues and standard additions. Standard additions provided the best results for unfiltered samples. Finally, filtered and unfiltered samples were analyzed using both polyethersulfone preconcentration and membrane‐assisted solvent extraction and results showed a good agreement between the two methods. In both cases unfiltered samples provided concentrations 1.5–2.6 times higher than filtered samples.